The truth about you : things you don't know you know - Bauer, Mary M., 1958- (Acton, Mass. : VanderWyk & Burnham, 2006)
"Deconstructing beliefs the author calls myths, this self-help book encourages the reader to stop being afraid and start being who they wish to. The theme: You are in charge of your reality. Thoughts, when combined with words and actions, create the experience. Only you can think your thoughts, say your words, decide what actions you will take"--Provided by publisher.
Life is for you to decide -- Are you making God too human? -- Remember your true nature -- Reconsider your childhood -- Wellness is your natural state -- All relationships are holy -- Create the life of your dreams -- Recognize the fear illusion -- Happiness is a choice.
Includes bibliographical references (p. 181-182) and index.
Keywords: Self-actualization (Psychology)